2020
DOI: 10.1158/1538-7445.tumhet2020-po-120
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PO-120: MYC drives temporal evolution of small cell lung cancer subtypes by reprogramming neuroendocrine fate

Abstract: Small cell lung cancer (SCLC) is a highly aggressive neuroendocrine tumor that is treated clinically as a single disease with poor outcomes. However, SCLC is recently recognized to comprise multiple molecular subsets with unique therapeutic vulnerabilities. Four distinct subtypes of SCLC have been defined based on expression of lineage-related transcription factors: ASCL1, NEUROD1, POU2F3 or YAP1. The origins of these subtypes remain unknown. We use mouse and human SCLC models with a time-series analysis of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Apart from its clinical value, we proposed the relationship between the so-called "SCLC transformation" in clinical and C-NEC because a subtype classification for SCLC has recently been proposed based on the high levels of key transcriptional regulators, namely ASCL1 (SCLC-A), NEUROD1 (SCLC-N), POU2F3 (SCLC-P), and YAP1 (SCLC-Y) [41]. Irlend et al observed that MYC activates NOTCH signaling to dedifferentiate tumor cells from ASCL1+ to NEUROD1+ to the YAP1+ state, and they proposed that SCLC molecular subtypes are not distinct but instead show a dynamic stage of tumor evolution [42]. Doron Tolomeo et al [43] found that plasmacytoma variant translocation 1 (PVT1) transcripts underlie a functional connection between MYC and YAP1/POU2F3, suggesting that they contribute to the transcriptional landscape associated with MYC amplification.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its clinical value, we proposed the relationship between the so-called "SCLC transformation" in clinical and C-NEC because a subtype classification for SCLC has recently been proposed based on the high levels of key transcriptional regulators, namely ASCL1 (SCLC-A), NEUROD1 (SCLC-N), POU2F3 (SCLC-P), and YAP1 (SCLC-Y) [41]. Irlend et al observed that MYC activates NOTCH signaling to dedifferentiate tumor cells from ASCL1+ to NEUROD1+ to the YAP1+ state, and they proposed that SCLC molecular subtypes are not distinct but instead show a dynamic stage of tumor evolution [42]. Doron Tolomeo et al [43] found that plasmacytoma variant translocation 1 (PVT1) transcripts underlie a functional connection between MYC and YAP1/POU2F3, suggesting that they contribute to the transcriptional landscape associated with MYC amplification.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin (a common platinum-based chemotherapy) resistance in particular is thought to be a result of lung cancer with a more oxidative phenotype, characterized by increased mitochondrial density, ROS, and dependence on glutamine and fatty acid oxidation mechanisms (102)(103)(104)(105). Carboplatin (another platinum-based chemotherapy) resistance, however is associated with a greater dependence on glycolysis, possibly mediated by MYC expression (102,106,107). It is unclear whether these profound differences in resistance mechanisms are due to metabolic reprogramming events triggered by the treatment or whether the treatment selectively targets cells utilizing specific pathways from a metabolically heterogeneous population.…”
Section: Metabolic Implications Of Therapy In Lung Cancer Fueling Resistance: Metabolic Alterations and Standard Of Carementioning
confidence: 99%